Assessment of Adherence to ACC/AHA Guidelines in Primary Management of Patients With NSTEMI in a Referral Cardiology Hospital. Issue 1 (March 2015) - Farahzadi, Mohammadreza; Shafiee, Akbar; Bozorgi, Ali; Mahmoudian, Mehran; Sadeghian, Saeed
Abstract : Acute coronary syndromes are considered as a global major health-care problem, and Iran as a developing country is of no exception. We aimed to investigate the degree of adherence to American College of Cardiology and American Heart Association (ACC/AHA) guideline for the management of non–ST-segment elevation myocardial infarction (NSTEMI) in patients who presented to the emergency department at Tehran Heart Center. Data of the patients who presented with acute chest pain to the emergency department of Tehran Heart Center within 1 year and were diagnosed as NSTEMI by the cardiologist in charge were included. The details of the initial managements based on the ACC/AHA guideline for NSTEMI of the patients were recorded from the patients' files in the emergency department for this study. Then, the frequency of guideline-related management in the study population was calculated and reported. A total of 684 patients [mean age = 62.95 ± 12.19 years; male gender = 460 (67.3%)] were diagnosed as NSTEMI at the emergency department of our center. Initial management based on the current guideline including administration of aspirin and clopidogrel was performed in 98.4% and 95.0%, respectively. Intravenous heparin was administered in 67.0% of the patients, whereas 30.8% of patients received enoxaparin. Following the initial management, coronary angiography was performed in 563 (82.3%) patients within 48 hours from the admission. Adherence to ACC/AHA guideline for the management of NSTEMI in patients who presented to a tertiary health-care center was in a high degree.